Hooker the Theologian - Williams, Rowan (Journal of Anglican studies, 2003)
For Hooker's opponents, sacraments could only be human actions designed to further the homogeneity of that community of uniform spiritual achievement which is the holy congregation. Hooker, on the other hand, affirms the possibility of uneven, confused faith, even the confused ecclesial loyalties of the ‘church papist’, as something acceptable within the reformed congregation. This is entirely of a piece with the defence of a liturgy that is more than verbal instruction. Hooker traces these two issues to a Christology which is centred upon divine gift and ontological transformation, and a consequent sacramental theology which affirms the hiddenness but effectiveness of divine presence and work in the forms of our ritual action.